Advancements in Quadcopter Development through Additive Manufacturing: A Comprehensive Review - Idris Seidu; Benjamin Olowu; Samuel Olowu (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The paper provides a comprehensive review of the advancements in quadcopters development made possible through additive manufacturing (AM). The review begins with an introduction to quadcopter technology and the basics of AM, followed by an exploration of the various AM technologies and materials used for creating quadcopter components. It highlights the innovative designs and complex geometries enabled by AM, as well as the improvements in customization and integration of multiple functions into single components. Practical case studies demonstrate the application of AM in producing high-performance quadcopters for various sectors, including military, commercial, research, and recreational use. The paper also addresses the technical challenges, economic considerations, and regulatory issues associated with AM in quadcopter development. Finally, it discusses future trends and research directions, emphasizing the potential of emerging materials and technologies to further enhance quadcopter performance. This review underscores the significant impact of AM on the evolution of quadcopters and the importance of ongoing research in this field.